Penyuluhan Edukasi Jamur Kulit Dan Upaya Pencegahannya Pada Ibu- Ibu Kelompok Pengajian Desa Karang Sari, Kecamatan Jati Agung - Emantis Rosa; Yulianti; M. Kanedi; Selvi Marcelia; Linda Septiani (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Toadstools can live everywhere in various ecosystems, with various habitats, one of which can infect the skin. The skin is an important part of the human body, because the skin acts as a protector for the body's internal organs, on the other hand, the skin is also a part of the body that is quite sensitive to several infectious diseases rather than microorganisms such as viruses, bacteria and fungi. This outreach activity aims to provide education to the community about knowledge and understanding of the fungus as well as efforts to prevent it among the women of the Koran Sari Village study group, Jati Agung Region. The results of this activity assessment show an increase from 45.3% to 77.3% with an average increase of 30.6%, whereas from the results of the assessment process the criteria for paying attention, asking, giving opinions and answering questions is more than not paying attention, not asking, and not giving opinions and not answering.